IFRS adoption and accounting conservatism in Latin America. Issue 3 (3rd July 2020) - Lopez, Harold; Jara, Mauricio; Cabello, Adriana
Abstract : Purpose: The purpose of this paper is to analyze the impact of IFRS mandatory adoption on accounting conservatism and to shed light on the drivers of such impact. Design/methodology/approach: Using a sample of listed firms for five Latin American countries, the authors analyze the relation between mandatory adoption of International Financial Reporting Standards and the conditional accounting conservatism of earnings. Findings: The authors find evidence that IFRS adoption boosts earnings conservatism. This result is robust and heterogeneous. The results also show that the effect of IFRS differs across firms and countries. Specifically, the impact of IFRS adoption is higher for low-earnings-quality firms and for firms with high levels of investment opportunities. Practical implications: The results suggest that IFRS adoption in Latin America has enhanced comparability of financial information both across and within countries. Originality/value: This paper contributes to the literature by providing new evidence on the drivers of the impacts of IFRS adoption in emerging markets. Abstract : Propósito: Este artículo analiza el impacto de la adopción obligatoria de las Normas Internacionales de Información contable (IFRS o NIIF) en el conservadurismo contable y aclara los determinantes de dicho impacto. Diseño/metodología/enfoque: Usamos una muestra de empresas listadas en cinco países latinoamericanos para analizar la relación entre la adopción obligatoria de IFRS y el conservadurismo contable condicional. Resultados: Encontramos evidencia de que la adopción de IFRS aumenta el conservadurismo contable. Este resultado es robusto y heterogéneo. Nuestros resultados también muestran que el efecto de IFRS en conservadurismo difiere entre empresas y países. En particular, el impacto de IFRS es mayor para firmas con baja calidad contable y altos niveles de oportunidades de inversión. Implicancias prácticas: Nuestros resultados sugieren que la adopción de IFRS en Latinoamérica fomentó la comparabilidad de los estados financieros tanto intra como entre países. Originalidad/valor: Nuestro estudio contribuye a la literatura proveyendo evidencia nueva sobre los determinantes de los impactos de la adopción de IFRS en mercados emergentes.